2016
DOI: 10.5937/industrija44-10309
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of credit growth to nonfinancial companies in B&H

Abstract: Non-financial sector in B&H and the companies due to lack of its own funds for sustainable growth rely on financing its operations through bank loans. The dominant share of lending to banks in B&H is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…the increase of credit activities might positively impact the quality of loan portfolio of a banking sector. This result ws confirmed in empiric bibliography, and it was also reached by Boudriga, Taktak & Jellouli (2009) and Ganic (2014) i Alihodžić & Plakanović (2016).…”
Section: Source: Authors' Researchsupporting
confidence: 68%
“…the increase of credit activities might positively impact the quality of loan portfolio of a banking sector. This result ws confirmed in empiric bibliography, and it was also reached by Boudriga, Taktak & Jellouli (2009) and Ganic (2014) i Alihodžić & Plakanović (2016).…”
Section: Source: Authors' Researchsupporting
confidence: 68%
“…A high inflation rate will exacerbate economic slowdown, as evidenced by the Asian crisis in 1998. The field has studied inflation as a variable that affects the lending (Akani & Onyema, 2017;Alihodzic & Plakalovic, 2016;Lee, 2016).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…They found that credit to the private sector positively relates to the nonperforming loan ratio, total deposits, and interbank and inflation rates. Alihodzic & Plakalovic (2016) showed that operating costs, the consumer price index, real GDP growth, deposit interest rate, interest rate, deposit growth rate, and non-performing loans are independent variables, while the loans growth rate can be used as the dependent variable.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In general, the dynamics of credit growth throughout the period applied almost equally to the private sector of the company (Alihodžić, & Plakalović, 2016, Alihodžić, 2018 and to citizens. At the same time, the pronounced dynamics of lending sometimes led to the entry into a moral hazard and, in the end, to the collapse of several banks in B&H (Plakalović & Alihodžić 2015, Krunić, 2014.…”
Section: Dynamics Of Consumer Credit Growthmentioning
confidence: 99%